Przyśrodkowa transpozycja włókien rozszczepionego mięśnia prostego bocznego w całkowitym porażeniu nerwu okoruchowego – opis przypadku - Pelińska, Katarzyna; Ordon, Agata; Loba, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
Complete oculomotor nerve palsy involves loss of function of as many as four out of six extraocular muscles, levator palpebrae superioris, and intraocular muscles, i.e. pupillary sphincter and ciliary muscle. Surgical treatment options are very limited as the superior oblique muscle and the lateral rectus muscle innervated by separate nerves are the only extraocular muscles whose function is not compromised. This article presents a case study of complete oculomotor nerve palsy following a neurosurgical procedure managed by medial transposition of the lateral rectus muscle with very satisfying outcomes.